Compulsive hoarding and acquiring : therapist guide - Steketee, Gail (Treatments that work., 2007)
Describes an empirically-validated treatment program for use with those individuals who suffer from compulsive hoarding, excessive acquiring, and problems with discarding. Based on the principles of cognitive-behavioral therapy, this guide provides clinicians with the tools and information to help clients restructure their thoughts.